Isolation and Identification Of Triterpenoid Saponin From Baringtonia asiatica Kurz Seeds. - Tanor, Meity N; Abadi, Abdul Latief; Rahardjo, Bambang Tri; Pelealu, Jantje (Journal of Tropical Life Science, 2014)
The study aimed to identify the content of the triterpenoid saponin compound from Barringtonia asiatica seeds collected from coastal of Malalayang beach, Manado, North Sulawesi. The method of extraction was the maceration with methanol solvent. The identification of the isolate was by thin layer chromatography, column chromatography, and GCMS. The phytochemistry test result of B. asiatica seed extract contained the compounds of alkaloid, saponin, and tannin. Then, the compound was separated by a thin layer chromatography method with a solvent system of methanol:chloroform:water. It produced three nodes that were spread around polar (Rf 0.24), semipolar (Rf 0.6) and non-polar (Rf 0.78) areas. Meanwhile, the process of column chromatography could only separate two chemical components namely semipolar (Rf 0.6) and polar (Rf 0.76). The identification with GCMS resulted in three compounds of Triterpenoid saponins, namely 2.4-bis-(1.1-dimethyl ethyl); 4-Dodecylphenol; and 2.6 bis-(1.1-dimethyl ethyl-4-methyl).